Comparison of the Agency for Healthcare Research and Quality Patient Safety Indicator Rates Among Veteran Dual Users. (July 2014) - Chen, Qi; Hanchate, Amresh; Shwartz, Michael; Borzecki, Ann M.; Mull, Hillary J.; Shin, Marlena H.; Rosen, Amy K.
This study compares rates of 11 Agency for Healthcare Research and Quality Patient Safety Indicators (PSIs) among 266 203 veteran dual users (ie, those with hospitalizations in both the Veterans Health Administration [VA] and the private sector through Medicare fee-for-service coverage) during 2002 to 2007. PSI risk-adjusted rates were calculated using the PSI software (version 3.1a). Rates of pressure ulcer, central venous catheter-related bloodstream infections, and postoperative sepsis, areas in which the VA has focused quality improvement efforts, were found to be significantly lower in the VA than in the private sector. VA had significantly higher rates for 7 of the remaining 8 PSIs, although the rates of only 2 PSIs (postoperative hemorrhage/hematoma and accidental puncture or laceration) remained higher in the VA after sensitivity analyses were conducted. A better understanding of system-level differences in coding practices and patient severity, poorly documented in administrative data, is needed before conclusions about differences in quality can be drawn.